EVALUATION OF CONTENT AND NATURE OF THE SPATIAL DISTRIBUTION OF HEAVY METALS (CO, ZN, PB, CD, NI, CU) IN THE WATER AREA OF AGRAKHANSKY BAY - G. M. Abdurakhmanov; A. A. Gadzhiev; E. M. Medzhidova; Sh. M. Samudov; Yu. G. Yusupov (Юг России: экология, развитие, 2014)
The article presents data on the content and nature of the spatial distribution of heavy metals (Co, Zn, Pb, Cd, Ni, Cu) in the waters of the Agrakhanskiy Gulf.